LncRNA NONRATT021972 Was Associated with Neuropathic Pain Scoring in Patients with Type 2 Diabetes - Wei Yu; Guo-qing Zhao; Rang-juan Cao; Zhi-hua Zhu; Kai Li (Behavioural Neurology)
Background. Long noncoding RNAs were involved in the processes of diabetes. Our study was aimed to explore clinical potential of LncRNA NONRATT021972 in diabetic neuropathic pain and investigate detailed mechanisms. Methods. 154 patients with type 2 diabetes were enrolled as experimental group paired with control. Patients without diabetes but neuropathy were enrolled to explore exclusive role of LncRNA NONRATT021972 in neuropathy. Real-time PCR and ELISA were performed to examine expression of LncRNA and TNF-α in flood. Neuropathic pain scores were calculated with data from NPQ. Streptozotocin was used for SD adult male rats to establish diabetes for NONRATT021972 siRNA or saline treatment. Neuropathic pain behaviors and expression of TNF-α were assessed. Result. Patients with type 2 diabetes had a significantly higher concentration of LncRNA NONRATT021972 in blood and more severe symptoms of neuropathic pain. LncRNA NONRATT021972 was positively associated with neuropathic pain scores of type 2 diabetes. TNF-α level increased in patients with type 2 diabetes. Animal experiment showed that LncRNA NONRATT021972 siRNA attenuated inflammation via decreasing TNF-α and alleviated neuropathic pain. Conclusion. LncRNA NONRATT021972 increased in type 2 diabetes and was positively associated with neuropathic pain scoring in type 2 diabetes. LncRNA NONRATT021972 exacerbated neuropathic pain via TNF-α related pathways.